An Overview of the Loading Efficacy of Cationic Lipids with Milk Proteins: A Potential Application for Lipid Delivery - Chanphai, Penprapa; Bourassa, Philippe; Tajmir-Riahi, Heidar A. (Current Medicinal Chemistry, 2020)
In this review, the loading efficacies of helper and Cationic Lipids Cholesterol (CHOL), 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP), Dioctadecyl Dimethyl- Ammonium Bromide (DDAB) and Dioleoyl Phosphatidylethanolamine (DOPE) with milk β- lactoglobulin, α-casein and β-casein were compared in aqueous solution at physiological conditions. Structural analysis showed that lipids bind milk proteins via hydrophilic, hydrophobic and H-bonding contacts with DOTAP and DDAB forming more stable protein conjugates. Loading efficacy was 30-50% and enhanced with cationic lipids. Lipid conjugation altered protein conformation, causing a partial protein structural destabilization. Milk proteins are capable of transporting lipids in vitro.
Keywords: loading efficacy